Susceptibility tests of the house fly adults, Musca domestica to Bacillus thuringiensis - Habib, M. E. M.; Garcia, M. A. (Anais da Sociedade Entomológica do Brasil, 1976)
Susceptibility tests of Musca domestica adults to Bacillus thuringiensis in a fom of a biobacterial preparation, or insecticide "BIOTROL XK", proved that the LD50, LD70 and LD90 after 24 hours were 5.35 x 109; 7.5 x 109 and 1,09 x 109 viable spores/gm. After 48 hours, the same doses were 3.84 x 109; 5.54 x 109 and 7.75 x 109. After 72 hours, the doses were 3.31 x 109; 4.89 x 109 and 6.91 x 109. Finally, the same doses after 96 hours were 2.69 x 109; 3.86 x 109and 5.62 x 10 9viable spores/gm. respectively. The adults were infected per os. The biological preparation could not be recommended in the biological control of this insect without studying the susceptibility of its larval instars to the samee preparation.